STRATEGI KOMUNIKASI DALAM MENCEGAH KERUSUHAN DI LEMBAGA PEMASYARAKATAN - Graciella Devi Maharani (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
In Indonesia, it is not uncommon to hear news about the Correctional Institutions riots. There have been recorded several cases of riots in 2020, for example Lembaga Pemasyarakatan Class I Cirebon, Lembaga Pemasyarakatan Class II A Manado, etc. Such riots were triggered by sensitivity due to friction between the Prison-Based Prisoners and Correctional Officers and among Correctional Prisoners. Therefore special attention is needed regarding this problem with prevention so that the prison environment remains conducive, one of which is the communication strategy. The purpose of this research is to find out how the communication strategy is in preventing riots in prisons. This research uses qualitative methods and data collection techniques of literature study. The results of the study found a strategy by utilizing daily interactions between inmates and officers as well as between inmates. The use of communication strategies can be one of the important efforts to prevent riots in prison. So that understanding of communication strategies needs to be considered by officers for a conducive prison environment.